2008
DOI: 10.2741/2951
|View full text |Cite
|
Sign up to set email alerts
|

The p38 MAPK stress pathway as a tumor suppressor or more?

Abstract: Abstractp38 mitogen-activated protein kinases (p38 MAPKs) are a group of serine/threonine protein kinases that together with ERK (extracellular signal-regulated kinases) and JNK (c-Jun N-terminal kinases) MAPKs act to convert different extracellular signals into specific cellular responses through interacting with and phosphorylating downstream targets. In contrast to the mitogenic ERK pathway, mammalian p38 MAPK family proteins (alpha, beta, gamma, and delta), with and without JNK participation, predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 119 publications
(152 reference statements)
3
86
0
Order By: Relevance
“…p38 MAPKs consist of four family members (␣, ␤, ␥, and ␦) in which p38␣ is ubiquitously present, whereas p38␥ is highly expressed in certain cancers (3). In addition to well established regulatory effects in cytokine signaling and stress response, substantial evidence suggests that the p38␣ pathway functions as a tumor suppressor (4 -8).…”
Section: Mapksmentioning
confidence: 99%
“…p38 MAPKs consist of four family members (␣, ␤, ␥, and ␦) in which p38␣ is ubiquitously present, whereas p38␥ is highly expressed in certain cancers (3). In addition to well established regulatory effects in cytokine signaling and stress response, substantial evidence suggests that the p38␣ pathway functions as a tumor suppressor (4 -8).…”
Section: Mapksmentioning
confidence: 99%
“…Phosphatidylinositol-3 kinase (PI3K) controls cell motility through the activation of protein kinase B (Akt) and other targets (19,20); however, cell-dependent differences in these regulatory mechanisms exist (18,(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we have shown that p38␥ is selectively activated by TAM and that p38␥ activity is necessary and sufficient to stimulate ER/Ser-118 phosphorylation and to confer SERM sensitivity. Because p38␥ and p38␣ activities are antagonistic (20,24,56) and because increased p38␣ activity is involved in TAM resistance in breast cancer cells and in patients (48,57), the hyperexpression of p38␥ may be a major determinant of breast cancer hormone sensitivity, both through stimulating the ER nonclassical pathway and through antagonizing p38␣ activity.…”
Section: Discussionmentioning
confidence: 99%
“…It possess both ERKlike mitogenic and p38-like stress kinase properties (20,21). Similar to ERK, p38␥ signals downstream of Ras to increase its transforming and invasive activities (22)(23)(24)(25).…”
Section: Estrogen Receptor ␣ (Er)mentioning
confidence: 99%